Civic Education Learning Management as a Builder of Student Character: Multi-Site Study in Several Public Elementary Schools in North Sulawesi Province - Mottoh, Yulmi Hesti; Lumapow, Harol R.; Rawis, Joulanda A M; Lengkong, Jeffry Sony Junus (JR Education, 2025)
This research aims to describe and discover the aspects of civic education learning planning, the implementation of civic education learning, the evaluation of civic education learning, and the development of civic education learning management as a character builder of students. This research method is relevant using the type of qualitative approach and case study method with the type of multi-case study design. This study found several things. First, PKn learning planning as a builder of students' character is shown in three categories of teachers' managerial dimensions, namely the role dimension, the process dimension, and the outcome dimension. Second, the implementation of PKn learning as a Character Builder for students is shown in four categories of teachers' managerial dimensions, namely the role dimension, the process dimension, the delivery dimension, and the use dimension. Third, the evaluation of Pkn learning as a builder of students' character is shown in three categories of teachers' managerial dimensions, namely the role dimension, the process dimension, and the method dimension. Fourth, the development of PKn learning management as a builder of students' character is shown in three categories of teachers' managerial dimensions, namely the role dimension, the process dimension, and the support form dimension. This study recommends several things. First, the role of teachers in planning, implementing, and evaluating PKn learning as a builder of student character found in this study is important to be disseminated or transferred to teachers in elementary schools who are not included in this study. Second, the process of planning, implementing, and evaluating PKn learning as a builder of student character found in this study is important to be transferred and used as a reference for elementary school teachers who were not included in this study. Third, PKn learning management as an efficient and effective builder of student character in elementary school requires development support from teachers, principals, the government, and technology.